ANALYSIS OF GENETIC VARIATION AMONG ACCESSIONS OF WILD AND CULTIVATED SPECIES OF AMARANTHUS BASED ON RAPD AND SDS-PAGE MARKERS - REEMA SRIVASTAVA; BIJOY K. ROY (International Journal of Pharma and Bio Sciences, 2012)
Genetic diversity and relationships among 12 cultivated and wild Amaranthus species were examined using protein and RAPD markers. High level of genetic diversity was common within species contrary to genetic uniformity within most accessions. On average, the polymorphism reached 42.60% among the cultivars but raised to 46.88% in the wild counterpart. The seed protein content varied in the 11.80-17% range and seeds of amaranth proved highly nutritive. The SDS-PAGE analysis indicated that such proteins in case of amaranths were highly heterogenous with 8-18 bands. Based on the electrophoretic mobility, such bands were assigned four zones (A, B, C and D). The RAPD analyses of Amaranthus species are further substantiated by the seed protein profile, indicating that a combination of such approaches can offer relatively reliable parameters to unravel genetic diversity.